The Role Of The National Navy (TNI AL) In Strengthening Maritime Domain Awareness In Indonesia - Budiman, Imam; Abdurachman, Bulbul; Nurhaliza, Aura (RMPI-BRIN, 2023)
The Indonesian Navy’s National Navy (TNI AL) has an important role in strengthening maritime domain awareness (MDA). In the era of globalization, the sea has become a very vital strategic area for the country. The Indonesian Navy has a major role in guarding and protecting Indonesian territorial waters from various threats, such as terrorism, illegal trade, illegal fishing, and conflicts at sea. To carry out this role, the Indonesian Navy needs good and effective MDA instruments. In building MDA, the Indonesian Navy must have the ability to collect information from various sources, be it through monitoring from the air, sea, or land. This paper uses a qualitative-descriptive method by obtaining data through a literature review process. The Indonesian Navy can utilize sea power to strengthen national defense, increase maritime trade, and secure marine resources. In this case, the Indonesian Navy can act as a protector of national security and also as a driver of economic growth through the maritime sector. In conclusion, TNI-AL plays a very important role in maritime domain awareness. For this reason, the TNI AL needs to have good and effective MDA instruments for gathering information and taking appropriate action. By having this capability, the Indonesian Navy can strengthen national defense and exploit the potential of the sea for the country’s economic progress.